Attitude towards health of young women with arterial hypertension - Larysa Ruban; Iryna Zharova (Kharkiv State Academy of Physical Culture, 2020)
Purpose: on the basis of a review of modern special literature and a questionnaire survey, to reveal the attitude to their health among young women with arterial hypertension. Material and methods: the reseach involved 40 women with a diagnosis of arterial hypertension, stage I at the age of 35-42 years, the duration of the disease is less than 3 years. The diagnosis was made by a family doctor, but drug therapy was not taken to correct blood pressure. The women had the following risk factors, namely, a decrease in the level of physical activity, inappropriate nutrition, excess weight, the presence of a large amount of stress in life, and smoking. In individual communication, we conducted a survey according to the method of R.A. Berezovskaya «Attitude to health». Results: the evaluation of the results was carried out on the basis of a qualitative analysis of the obtained data of the questionnaire in all areas of life. When asked about the most important values from all spheres of life, only 18 women rated their health as a factor important for them at a given moment in life. Content analysis of the definition of «Health» showed that 35% of women believe that this is the harmony of physical and mental well-being. 53% of women believe that lifestyle influences their health. Only 60% of the women surveyed by us in their daily life use recreational activities to maintain their health. Conclusions: the interviewed young women with arterial hypertension of the 1st stage do not follow the doctor's recommendations, do not undergo preventive examinations, do not follow a healthy lifestyle, and use recreational measures in small quantities. Modification of risk factors for arterial hypertension, development of educational and health-improving programs, aimed at increasing physical activity, will improve the quality of life of young people with hypertension.